2022
DOI: 10.1007/s13349-022-00618-9
|View full text |Cite
|
Sign up to set email alerts
|

Civil infrastructure defect assessment using pixel-wise segmentation based on deep learning

Abstract: Nowadays, the number of aging civil infrastructures is growing world-wide and when concrete is involved, cracking and delamination can occur. Therefore, ensuring the safety and serviceability of existing civil infrastructure and preventing an inadequate level of damage have become some of the major issues in civil engineering field. Routine inspections and maintenance are then required to avoid leaving these defects unexplored and untreated. However, due to the limitations of on-field inspection resources and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Hyperparameters are model parameters that need to be confirmed before training deep learning models, and their selection will affect results of the defect detection (Chou and Nguyen, 2022). Currently, most machine learning or deep learning models select empirical parameters for hyperparameters setting and optimization (Liu and Chou, 2023; Savino and Tondolo, 2023), which is difficult to achieve the optimal global solution, and the defect detection accuracy still has room for improvement. Bayesian optimization algorithm (BOA) has been widely used in machine learning (Lu et al, 2020) and has been shown to outperform random search, grid search, and human search in hyperparameters optimization (Xia et al, 2017), therefore it is introduced into the PSPNet.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperparameters are model parameters that need to be confirmed before training deep learning models, and their selection will affect results of the defect detection (Chou and Nguyen, 2022). Currently, most machine learning or deep learning models select empirical parameters for hyperparameters setting and optimization (Liu and Chou, 2023; Savino and Tondolo, 2023), which is difficult to achieve the optimal global solution, and the defect detection accuracy still has room for improvement. Bayesian optimization algorithm (BOA) has been widely used in machine learning (Lu et al, 2020) and has been shown to outperform random search, grid search, and human search in hyperparameters optimization (Xia et al, 2017), therefore it is introduced into the PSPNet.…”
Section: Methodsmentioning
confidence: 99%
“…Guo (Guo, 2022) integrates binocular and monocular cameras with the encoder-decoder network for automatic detection, ranging, and quantification of cracks as well as characterization of crack patterns. Aiming at cracks and delamination of infrastructure, Savino (Savino and Tondolo, 2023) developed a universal semantic segmentation network adapted to different image qualities, resolutions, and backgrounds. They introduced the ResNet50 module in the Deeplabv3+ network, utilized experience to set hyperparameters, and finally achieved a validation accuracy of 91.04%.…”
Section: Introductionmentioning
confidence: 99%
“…Models have been developed for automated detection, identification, and segmentation of infrastructure elements, such as segmenting the individual elements that can comprise a power utility pole [13], [9], [14], [15]. Deep learning is also being used for the detection and segmentation of defects in critical infrastructure including segmentation of cracks in concrete structures [16], [17], [18], or measurement of the inclination of utility poles [15].…”
Section: Introductionmentioning
confidence: 99%
“…The manual inspection of the bridge is always time-consuming and the result is inconsistent, subjective, and largely dependent on the experience and judgment of the inspector [2,3]. In addition, traditional bridge inspection is costly and associated with safety risks for the inspection crew and public.…”
Section: Introductionmentioning
confidence: 99%